AGBAR TOWER BY JEAN NOUVEL - Faccioli GABRIEL, Marcos (Revista Tópos, 2013)
Abstract This paper is an exercise to test a hypothesis, namely that the discourse of art criticism has any bearing at all on architectural works which have to respond to a vast array of conditions other than only to the aesthetical ones. As a matter of fact the aesthetic aspect of architectural works is often regarded as a quality that stands apart from all the others instead of being immersed with them and able to articulate all of them into a meaningful whole or image. The latter is the viewpoint we will strive to make sense of through the examination of one contemporary work that seems particularly apt to it, the Agbar Tower by Jean Nouvel. Keywords: architectural art criticism, architectural criticism, contemporary architecture. Resumo Este estudo é um exercício concebido para testar a hipótese de que o discurso da crítica de arte tem algo a dizer sobre obras arquitetônicas, as quais devem responder a todo um rol de condicionantes além dos puramente estéticos. De modo geral, o aspecto estético das obras arquitectônicas costuma ser considerado como fora e aparte dos demais condicionantes em vez de indissoluvelmente ligados a eles e capaz de articulá-los num todo significativo ou numa imagem. Esta última posição é aquela cujo sentido pretendemos investigar através do exame de uma obra contemporânea que parece, particularmente, requerer esse ponto de vista, a Torre Agbar de Jean Nouvel. Palavras-chave: crítica de arte da arquitetura, crítica de arquitetura, arquitetura contemporânea.